2020
DOI: 10.1111/jop.13123
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study reporting rituximab treatment for 33 patients with immunobullous disease

Abstract: Background Autoimmune bullous disorders, encompassing pemphigus and pemphigoid diseases, are associated with significant morbidity and mortality. This is in part due to high cumulative doses of corticosteroids in combination with immunosuppressant agents used in traditional treatment regimes. Rituximab is an antiCD20 monoclonal antibody which can induce complete remission, but it is currently unlicensed in the UK and approved only after other treatments have failed. Methods We report a retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…13 Watson et al reported a complete response rate of 27.3% on minimal therapy and a further 27.3% off therapy in patients received rituximab. 14 This data is compatible to our experience about therapeutic effect of rituximab in BP and some of their variants such as NP. However, it is not true about all of variants of BP, since we did not have any considerable response rate regarding lichen plan pemphigoides, which is another rare variant of BP and seems to be more likely to be resistant to treatment with rituximab.…”
supporting
confidence: 90%
“…13 Watson et al reported a complete response rate of 27.3% on minimal therapy and a further 27.3% off therapy in patients received rituximab. 14 This data is compatible to our experience about therapeutic effect of rituximab in BP and some of their variants such as NP. However, it is not true about all of variants of BP, since we did not have any considerable response rate regarding lichen plan pemphigoides, which is another rare variant of BP and seems to be more likely to be resistant to treatment with rituximab.…”
supporting
confidence: 90%
“…8 Watson et al reported a complete response rate of 27.3% on minimal therapy in patients received rituximab. 9 A rough comparison between these numbers and those belongs to our patients reveal the refractory nature of LPP compared to other forms of BP.…”
mentioning
confidence: 69%